BATH/ASME 2020 Symposium on Fluid Power and Motion Control 2020
DOI: 10.1115/fpmc2020-2767
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Efficient Energy Recovery Systems Using Digital Displacement® Hydraulics

Abstract: Heavy off-road vehicles using conventional hydraulic systems waste significant energy through the throttling of fluid to control the motion of their actuators. This paper demonstrates how Digital Displacement® Pump Motors (DDPMs) can be used to enable efficient hydraulic energy recovery systems for these vehicles by controlling the motion of actuators directly without the need of throttling. Experiments were carried out on a test rig consisting of a 10 tonne boom supported by a hydraulic ram des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In studies that focus on dynamic performance, very often a similar setup can be found with only one cylinder that applies the power-train concept of interest that has a mechanical load structure installed that involves realistic inertia and kinematic chains as on the real HDMM. In [16], for example, the original stick mechanism of a backhoe is incorporated into the test rig, and in [17], the full-size boom structure of a 16-tonne excavator is installed on a stationary rig for testing the lift cylinder. Still, those test rigs involve only one actuator, while the interest in this paper is on the interplay of multiple implement actuators.…”
Section: Experimental Approaches In Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In studies that focus on dynamic performance, very often a similar setup can be found with only one cylinder that applies the power-train concept of interest that has a mechanical load structure installed that involves realistic inertia and kinematic chains as on the real HDMM. In [16], for example, the original stick mechanism of a backhoe is incorporated into the test rig, and in [17], the full-size boom structure of a 16-tonne excavator is installed on a stationary rig for testing the lift cylinder. Still, those test rigs involve only one actuator, while the interest in this paper is on the interplay of multiple implement actuators.…”
Section: Experimental Approaches In Literaturementioning
confidence: 99%
“…Furthermore, the efficiency or consumption of the whole implement system with all major actuators is of interest; thus, boom, tilt, and telescope cylinders should be present in the setup connected by the real kinematic chains. Accordingly, setting up a test rig for a single actuator as in [14][15][16][17], would not be effective. Instead, an existing conventional nine-tonne telehandler has been chosen as the test platform, which can be seen in Figure 1, to incorporate the original kinematic chains, inertia, and control interface.…”
Section: Chosen Experimental Design For Rapid Yet Realistic Testingmentioning
confidence: 99%
“…Recent tests at Danfoss using a DDPM with a loaded linear actuator have shown that between 78%-88% of the energy originating from the prime mover can be recovered. 36…”
Section: The Worldwide Harmonised Light Vehicles Test Procedures (Wltp)mentioning
confidence: 99%
“…John Hutcheson et al utilized the digital displacement pump motor as a controlling element to directly control the motion of the actuator. Without throttling loss, the digital displacement system saved 1.1-10.8 times of energy through the comparison of their simulation outcomes [25]. Jill Macpherson et al carried out a backwardfacing simulation on an 18-ton excavator with the bus system architecture.…”
Section: Introductionmentioning
confidence: 99%